The Development of Lettuce (Lactuca Sativa) Vegetables Using a Hydroponic System in Narrow Home Gardens in Tanamodindi Sub-District, Palu City, Central Sulawesi - Arifuddin Lamusa; Faruq A.H Lamusa; Nur Risky Islianty (International Journal Of Community Service, 2024)
This community engagement activity was conducted on Merpati Street, Tanamodindi Sub-District, Palu City, Central Sulawesi Province, in collaboration with Internship Students (MBKM) from Tadulako University. The village faces issues regarding the utilization of narrow home gardens. The objectives of this community engagement are: 1) to enhance the knowledge of the surrounding community regarding the utilization of narrow home gardens to create added value for household income; 2) to promote vegetables as a nutritious source for consumption; 3) to increase the knowledge of both the community and students about effective hydroponic farming methods suitable for narrow home gardens. The method used in this activity was a participatory approach, where the team, MBKM students, and the surrounding community actively engaged in cooperative efforts. The primary targets of this training were students and community members involved in hydroponic vegetable cultivation in narrow home gardens on Merpati Street, Tanamodindi Sub-District, Palu City Central Sulawesi Province. The results of this community engagement activity include increased knowledge regarding using narrow home gardens for additional income generation and promoting nutritious vegetables for human consumption Education.